Penafsiran Pembatasan Hak Dipilih bagi Pejabat Negara: Mengkaji Ratio Decidendi Putusan Mahkamah Konstitusi - Nope, Bill; Redhani, Muhammad Erfa; Huda, Ni’matul; Hattabou, Anas (Fakultas Hukum Universitas Islam Indonesia, 2025)
The political right to be elected within the Indonesian constitutional practice in the aftermath of the Constitutional Court decision has led to a shifted paradigm. This article seeks to answer two questions, namely: First, why is there a shift of paradigm related to the right to be elected in the Constitutional Court Decision Number 68/PUU-XX/2022, especially regarding state officials who are not obliged to resign from their positions when they opt to become presidential and/or vice presidential candidates? Second, what is the legal impact of the Constitutional Court Decision Number 68/PUU-XX/2022 on state officials whom previously were required to resign by law? This article is the result of a doctrinal legal research that uses a case study approach, by examining the Constitutional Court decisions as the primary material. The study of the Constitutional Court's decision was carried out to analyse the considerations of the Constitutional Court justices ( ratio decidendi ) in issuing the said decision. This article concludes that: First, there has indeed been a shift of paradigm shift in the Constitutional Court by relaxing the restrictions on the right to be elected for state officials . The Constitutional Court views that in today's constitutional developments, it is no longer relevant to distinguish between the requirements for resignation for both elected and appointed officials. The Constitutional Court readjusts the right to be elected on the grounds that qualified human resources are needed to fill certain political positions and the right to be elected cannot be reduced due to the aforementioned circumstance in order to mitigate the risk of posing a form of discrimination. The legal impact that arose in the aftermath of the Constitutional Court's decision leads to a difference in treatment for a number of state officials/other public officials, namely that there remains a requirement to resign should they wanted to participate in political contests.Keywords: Right to be Elected, State Officials, Restrictions AbstrakHak untuk dipilih dalam praktik ketatanegaraan Indonesia, pasca putusan Mahkamah Konstitusi telah mengalami pergeseran paradigma. Artikel ini ingin menjawab dua pertanyaan yaitu: Pertama, mengapa terjadi perubahan paradigma berkaitan dengan hak dipilih dalam Putusan MK Nomor 68/PUU-XX/2022 khususnya mengenai pejabat negara yang tidak harus mundur dari jabatannya saat menjadi calon Presiden dan calon Wakil Presiden? Kedua, Apa dampak hukum dari Putusan MK Nomor 68/PUU-XX/2022 tarhadap pejabat negara yang diharuskan mundur oleh undang-undang? Artikel ini merupakan hasil riset hukum doktrinal menggunakan pendekatan kasus yaitu dengan mengkaji putusan-putusan MK sebagai bahan utama. Pengkajian terhadap putusan MK tersebut dilakukan untuk menganalisis berkaitan dengan pertimbangan hakim MK (ratio decidendi) dalam mengeluarkan putusan. Artikel ini menyimpulkan bahwa: Pertama, telah terjadi perubahan paradigma MK dengan memperlonggar pembatasan hak untuk dipilih bagi pejabat negara atau pejabat publik. MK memandang bahwa dalam perkembangan ketatanegaraan hari ini sudah tidak relevan untuk membedakan syarat-syarat mengundurkan diri baik pejabat yang dipilih maupun pejabat yang diangkat. MK memperlonggar hak dipilih tersebut dengan alasan bahwa diperlukan SDM yang berkualitas untuk mengisi jabatan-jabatan politik dan menurut MK hak untuk dipilih tidak dapat dikurangi karena jika hal tersebut dilakukan merupakan bentuk diskriminasi. Dampak hukum yang timbul pasca putusan MK tersebut yaitu terdapat perbedaan perlakuan bagi sejumlah pejabat negara/pejabat publik lain yaitu masih adanya syarat mengundurkan diri jika ingin mengikuti konstestasi politik.Kata Kunci: Hak Dipilih, Pejabat Negara, Pembatasan